PENERAPAN SISTEM BELAJAR LUAR KELAS UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS VIII MTS PONTIANAK - Juliyanti, Juliyanti; Aminuyati, Aminuyati; Khosmas, F.Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research is the increased interest and Social Science learning outcomes through the application of the system of learning beyond the classroom in grade VIII first semester at MTS Nurul Islam Pontianak 2018/2019 school year. This research is quantitative research using research methods-circling, the subject of the research is student grade VIII MTS Nurul Islam Pontianak this research sample amounted to 22 students. The data collected through direct observations, techniques/documentary studies, measurement techniques. Data analysis on the descriptive method is to do with the form used is the research Experiments (one group pre test post-tets). By using data collection tools in the form of direct observation techniques, and the study of documentary, to analyze the data in this study using a descriptive analysis, i.e. The descriptive analysis. The result value of pre-and post-test and calculation of test-t in the get the value of the sig (2-tailed) value pre-test and post-postal-test and smaller than 0.05 (0.00 ? 0.05), and this means that the hypothesis is a hypothesis that can be used alternative or Ha that is there is a difference in student learning outcomes learning IPS grade VIII in MTS Nurul Islam Pontianak which apply a system of learning beyond the classroom. The application of the system of learning outside of the classroom with the influence of the effect size that get results 1.90 meaning that learning outside of the classroom have effectiveness that belongs high on the learning outcomes of students in Science subjects Social class VIII in MTS Nurul Islam Pontianak.Keyword: System Of Learning Beyond The Classroom, Learning, Learning Outcomes, social science